2010
DOI: 10.1136/gut.2010.212555
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cells and hepatitis C: action and reaction

Abstract: In 1989, hepatitis C virus (HCV) was first identified as the infectious agent responsible for human non-A, non-B hepatitis. Two decades later, HCV remains a global public health problem with a suboptimal response rate to treatment and the absence of a protective vaccine. Recent work has highlighted the influence of the innate immune system, and in particular natural killer cells, on the outcome and pathology of HCV infection. These cells are considerably more complex than was originally thought and their role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 108 publications
(129 reference statements)
2
98
0
1
Order By: Relevance
“…Perturbations in NK cell frequency, phenotype, and function have been shown in chronically HCV-infected patients (30). The peripheral blood NK cell number and percentage of total lymphocyte population are lower in HCV-infected individuals (8). Additionally, the proportion of NKp30-and NKp46-expressing cells is reduced in patients with chronic hepatitis C (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perturbations in NK cell frequency, phenotype, and function have been shown in chronically HCV-infected patients (30). The peripheral blood NK cell number and percentage of total lymphocyte population are lower in HCV-infected individuals (8). Additionally, the proportion of NKp30-and NKp46-expressing cells is reduced in patients with chronic hepatitis C (31).…”
Section: Discussionmentioning
confidence: 99%
“…HCV affects NK cell activity through direct cell-to-cell interaction via CD81 or NK cell receptors or in an indirect manner via cytokine or TRAIL release (6)(7)(8)(9). HCV E2 glycoprotein is suggested to inhibit NK cells directly by cross-linking CD81 (6,10).…”
mentioning
confidence: 99%
“…+bright , but not the CD56 +dim subset, in patients with CHC compared to healthy individuals and spontaneous resolvers (4,28 (14). Moreover, they showed that the negative regulation of NK cells by CD94-NKG2A leads to altered NK-induced modulation of dendritic cell In conclusion, we found a significant imbalance between the CD56 +bright and CD56 +dim NK cell subsets in the liver of patients with recurrent CHC after LT compared to patients with CHC and normal donors for living donor LT. Because each NK cell subset has a distinct NK cell function, such an imbalance may result in altered immune responses against HCV, contributing to the progression of recurrent hepatitis C after LT.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies have revealed that functional impairment of innate immune cells, including NK and NKT cells, may be associated with the persistence of HCV infection (20). Particularly, NK cell function is attenuated in chronic HCV infection under the influence of cytokines, most likely through inefficient NK cell receptor-mediated stimulation (4,19). However, the involvement of NK cells in recurrent hepatitis C after LT remains unclear.…”
Section: Methodsmentioning
confidence: 95%
“…According to CD56 and CD16 expression, NK cells can be divided into three subsets: CD56 bri CD16 dim/neg (~10%), CD56 dim CD16 + (~90%) and CD56 neg CD16 + [8,9]. CD56 bri CD16 dim/neg subset produces cytokines such as IFNγ [10], CD56 dim CD16 + subset presents high cytotoxicity but little cytokine secretion [11], and CD56 neg CD16 + subset has been shown functionally deficient and is increased in chronic HIV and HCV infection [12].…”
Section: Introductionmentioning
confidence: 99%